Grounding Qur’anic Environmental Ethics among Karang Taruna Youth in Karta Raya Village: A Living Qur’an Study - Giyantara, Nanda; Badi’ah, Siti; Hendro, Beko (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2026)
The current ecological crisis suggests that public awareness of moral responsibility for protecting the natural environment remains insufficient. Increasing environmental degradation, including pollution, declining ecosystem quality, and weak ecological awareness, indicates that religious values concerning human responsibility toward nature have not been fully internalized in social practice, particularly among younger generations. The Qur’an contains environmental ethical values that provide a theological and moral foundation for sustaining ecological balance. This study examines how Qur’anic environmental ethics are actualized through a Living Qur’an approach among Karang Taruna youth in Karta Raya Village, Tulang Bawang Udik District, Tulang Bawang Barat Regency. It employs a qualitative design with a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation, and were analyzed descriptively and interpretively to identify the meanings and applications of Qur’anic values in youth social activities. The findings show that Karang Taruna youth translate Qur’anic values into ecological practices through three main forms: khilafah, which is actualized through collective clean-up activities and mosque-based environmental care; mizan, which is embodied in waste sorting and village-based waste management; and the prohibition of fasad, which is practiced through anti-pollution campaigns and irrigation-channel maintenance. The study contributes to Living Qur’an scholarship by showing how Qur’anic environmental values are received, internalized, and practiced through village youth activism. In this context, Karang Taruna youth function as local actors in ecological change who connect sacred texts with the practical needs of rural environmental management.